TEACHER AUTHENTICITY IN LANGUAGE EDUCATION - Jacobs, George M.; Asmawi, Adelina; Renandya, Willy A. (International Journal of Education, 2022)
In education, the phrase "authenticity" has various connotations, including in language education. This article begins by examining different meanings of the term authenticity in language teaching. Some of these meanings refer to authenticity in the assessment, tasks, and materials that language teachers use. The main part of the article looks at another meaning of authenticity. The literature on teacher authenticity and personal authenticity in general is applied to the situation of language teachers while viewing authenticity through the lens of student-centered learning (SCL) and the overall paradigm shift from which SCL grew. Topics discussed include whether teachers should behave according to students’ views of what teachers should do or according to how teachers themselves believe they should behave. The article next looks at how teachers can develop their authenticity via their lifelong, lifewide, and lifedeep learning. The article also delves into various issues in which teachers can be authentic by “walking their talk,” e.g., teachers who encourage students to read need to be readers themselves, and teachers who encourage their students to cooperate with their peers should cooperate with their own peers in education and elsewhere in their lives. The two final parts of the article ask what impact teacher authenticity might have on the teachers’ students and how authenticity, which seems to be such an individual construct, can be put to the service of society as a whole.